ANALISIS ASPEK FINANSIAL TERHADAP PERSISTENSI LABA - Sudiatmoko Sudiatmoko; Syamsuri Syamsuri; Suwarno Suwarno (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to examine the effect of book tax difference, operating cash flow and debt levels on earnings persistence.This research was conducted on 69 Real Estate companies listed on the Indonesia Stock Exchange, using a purposive sampling method through predetermined criteria. The data obtained were 19 companies that were used as research samples with observations for five years in the period 2014-2018, so that the total observations used were 95 samples. The data used are secondary data, namely the annual real estate company's financial statements for the period 2014-2018. Data analysis methods used are the t test and F test. The results showed, based on the results of the t test, it was found that the book tax difference had no effect on earnings persistence, operating cash flow had a positive and significant effect on earnings persistence and the level of debt had a positive and significant effect on earnings persistence, and based on the results of the F test test it was found that the book tax difference, operating cash flow and debt levels simultaneously have a positive and significant effect on earnings persistence